Skill-learning by observation-training with patients after traumatic brain injury - Avraham, Einat; Sacher, Yaron; Maaravi-Hesseg, Rinatia; Karni, Avi; Doron, Ravid (Frontiers in Human Neuroscience, 2022)
Traumatic brain injury (TBI) is a major cause of death and disability in Western society, and often results in functional and neuropsychological abnormalities. Memory impairment is one of the most significant cognitive implications after TBI. In the current study we investigated procedural memory acquisition by observational training in TBI patients. It was previously found that while practicing a new motor skill, patients engage in all three phases of skill learning–fast acquisition, between-session consolidation, and long-term retention, though their pattern of learning is atypical compared to healthy participants. A different set of studies showed that training by observing a motor task, generally prompted effective acquisition and consolidation of procedural knowledge in healthy participants. The aim of our study was to (i) evaluate the potential benefit of action observation in TBI patients. (ii) Examine the possibility of general improvement in performance between the first (24 h post-training) and second (2 weeks post-training) stage of the study. (iii) Investigate the link between patients’ ability to benefit from observational learning (via performance gains–speed and accuracy) and common measures of injury (such as severity of injury, functional and cognitive measures). Materials and methods Patients hospitalized after moderate to severe TBI, were trained by observation for the finger opposition sequence (FOS) motor task. They were then tested for the observation-trained sequence (A) and a similar control sequence (B), at two different time-points (24 h post-training and 2 weeks later). Results revealed (i) a significant difference in performance between the trained (A) and untrained (B) sequences, in favor of the trained sequence. (ii) An increase in performance for both sequences A and B toward the second (retention) session. (iii) The advantage for sequence A was stable and preserved also in the second session. (iv) Participants with lower moderate Functional Independence Measure (FIM) scores gained more from observational-procedural learning, compared with patients with higher functional abilities. Conclusion Overall, these findings support the notion that TBI patients may achieve procedural memory consolidation and retention through observational learning. Moreover, different functional traits may predict the outcomes of observational training in different patients. These findings may have significant practical implications in the future, regarding skill acquisition methods in TBI patients.